Immediate ART and clinical outcomes in New York City among patients newly diagnosed with HIV. Issue 4 (3rd April 2023) - Mgbako, Ofole; Mathu, Rachel; Gonzalez Davila, Mila; Mehta, Monica; Cabrera, Joselyn; Carnevale, Caroline; Zucker, Jason; Gordon, Peter; Olender, Susan
ABSTRACT: Immediate antiretroviral therapy (iART) has been shown to decrease time to viral suppression. Our center underwent significant practice transformation to support iART, including a same-day Open Access (OA) model and enhanced care coordination. We examined whether same-day ART at linkage was associated with favorable proximate and long-term HIV care outcomes. From 2018 to 2019, patients newly diagnosed with HIV, linked to care at our institution, and iART eligible were included. We evaluated the association between iART and time to viral suppression, and between iART and initial/sustained viral suppression and retention in care. We also evaluated the association between use of OA and frequency of care coordination with the same outcomes. Of the 107 patients included, 72 initiated same-day ART at linkage and 35 did not. There was no statistically significant differences in whether patients were ever suppressed, had sustained viral suppression, or were retained in care between those who received same-day ART and those who did not. More care coordination was associated with retention in care (RR 1.21 [1.01–1.5]; p = 0.05). Organizing vital services and ensuring implementation strategies that facilitate iART, while tailoring the approach to the patient's comfort level, is likely optimal for longitudinal HIV care engagement.